Correlation Between Quantitative Uptake of 99mTC-DPD and Echocardiographic Parameters in Cardiac ATTR: A Novel Follow-Up Strategy - Mehmet Harapoz; Mehmet Harapoz; Scott Evans; Paul Geenty; Paul Geenty; Fiona Kwok; Fiona Kwok; Graeme Stewart; Graeme Stewart; Graeme Stewart; Mark S. Taylor; Mark S. Taylor; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: There has been a paradigm shift in diagnosis of cardiac transthyretin amyloidosis (ATTR) with non-invasive techniques including technetium-99m 3,3-diphosphono-1,2-propanodicarboxylic acid (99mTc-DPD) bone scintigraphy. We evaluated structural and functional biventricular alterations by transthoracic echocardiography (TTE) and determined the correlation with 99mTc-DPD tracer uptake in ATTR.Materials and Methods: ATTR patients (wild-type, hereditary or asymptomatic transthyretin [TTR] variant carriers) with 99mTc-DPD and TTE were selected; 99mTc-DPD uptake was analyzed quantitatively. TTE assessment of left ventricle (LV) and right ventricle (RV) parameters was performed.Results: Forty ATTR patients (wild-type n = 17; hereditary ATTR and TTR variant carriers n = 23; median age 68.8 ± 22 years) were included. TTE parameters displaying good correlation with 99mTc-DPD tracer uptake included LV average wall thickness (r = 0.837), LV indexed mass (LVMI; r = 0.802), RV wall thickness (r = 0.610), average e' (r = −0.830), E/e' ratio (r = 0.786), LV global longitudinal strain (GLS; r = 0.714) and RV GLS (r = 0.632; p < 0.001 for all). Hereditary ATTR and TTR variant carriers without cardiac tracer uptake had normal echocardiographic parameters. Receiver operating characteristic curves demonstrated strong diagnostic accuracies for structural (LV wall thickness, LVMI and RV wall thickness; area under the curve (AUC) of 0.96 for all) and functional (LV and RV GLS; AUC of 0.86 and 0.88, respectively) parameters.Conclusion: Good correlations between TTE biventricular structural and functional parameters were demonstrated with quantitative 99mTc-DPD uptake. Echocardiography may potentially assume a significant role in longitudinal follow-up for monitoring disease progression and for evaluating treatment response.